PKM (Pengabdian Kepada Masyarakat) PENGARUH PROMOSI TERHADAP HASIL WIRAUSAHA STUDI KASUS DI KOPERASI AGRO RIMBA NUSANTARA (AGRINA) - Nasution, Nurlaila; Tambunan, Agustina (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
This article discusses the effect of promotion on entrepreneurial outcomes carried out at the Agro Rimba Nusantara (AGRINA) Cooperative in Parsalakan village. Products from salak products are still difficult to find, especially Padangsidimpuan. It is still difficult to find in shops selling products from Koperasi Agro Rimba Nusantara (AGRINA). The lack of promotion made the public less familiar with the products marketed by the Agro Rimba Nusanta Cooperative (AGRINA). One solution that can be done is to increase promotions such as on social media, whether on Facebook, Instgram, Twitter, Whatsaap, joining buying and selling groups and even collaborating with shops in various regions. The purpose of holding this promotion is so that people are more familiar with the products made by the Agro Rimba Nusantara Cooperative (AGRINA) so that they can increase sales. The method of implementation is by presenting the material using the media percentage (PPT) through the help of Infocus, LCD and sound system. Meanwhile, the tools and materials used are print out of the material presented. The result of this activity was the enthusiasm of the participants at the Agro Rimba Nusantara Cooperative (AGRINA) in listening to the material presented by the speakers and the questions and answers between the presenters and the participants in the Agro Rimba Nusantara Koprasi, Parsalakan Village, Angkola Barat Tapanuli Selatan District.